Kartäusische Gebetbücher. Zur Kohärenz von Bibliotheksordnungen in den Kartausen Basel und Erfurt - Ubl, L (LIT Verlag, 2023)
This article examines the metaphorical and literal position of prayer books within the Carthusian order and, more specifically, in the Charterhouses of Erfurt and Basel. By looking at the library catalogues of both institutions, the perspective will be directed at the revelations associated with the nuns of Helfta. Analysing their position in the library shelves as well as the way in which the works are indexed will provide insights into how these texts were read and perceived. Nowadays classified as ‘mystical’ texts, it can be seen that different versions of these texts can be situated within wider devotional contexts and cultures. Conversely, the intertwining perspective on institutional organisation and individual texts allows a more multi-faceted view on prayer books as a genre. Thus, the article highlights the importance of reception history within particular institutions, as their methods of categorisation and, following on that, perceptions of a text might display hitherto unknown incoherences and varieties. Books containing prayers are, due to their quantity, a promising starting point for further studies in this area.